Updates in venous thromboembolism management: evidence published in 2017. Issue 4 (8th August 2018) - Bartlett, Matthew A.; Bierle, Dennis M.; Saadiq, Rayya A.; Mauck, Karen F.; Daniels, Paul R.
ABSTRACT: Venous thromboembolism (VTE) management is rapidly evolving and staying up-to-date is challenging. We identified the most practice-informing articles published in 2017 relevant to the nonspecialist provider managing VTE. We performed a systematic search of the literature (Appendix A), limiting the search to a publication date of 2017. Two reviewers screened the 2735 resulting abstracts to identify high-quality, clinically relevant publications related to VTE management. One-hundred and six full-text articles were considered for inclusion. The five authors used a modified Delphi method to reach consensus on inclusion of seven articles for in-depth appraisal, following predetermined criteria of clinical relevance to nonspecialist providers, potential for practice change, and strength of the evidence.